2013
DOI: 10.1039/c3sm50298h
|View full text |Cite
|
Sign up to set email alerts
|

Granular materials composed of shape-anisotropic grains

Abstract: Granulate physics has made considerable progress during the past decades in the understanding of static and dynamic properties of large ensembles of interacting macroscopic particles, including the modeling of phenomena like jamming, segregation and pattern formation, the development of related industrial applications or traffic flow control. The specific properties of systems composed of shape-anisotropic (elongated or flattened) particles have attracted increasing interest in recent years. Orientational orde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
92
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(103 citation statements)
references
References 168 publications
3
92
1
1
Order By: Relevance
“…Due to dynamics in continuous shearing, this ordering phenomenon emerges even in systems composed of particles with very low platyness with a shape differing only slightly from spherical shape. This kind of ordering has previously been observed in experiments [27,22] and numerical simulations mainly with two-dimensional elongated particles [28,15,18]. Regarding the privileged direction of alignment, we found that, as platyness increases, this direction gradually changes from that of the major principal stress to a direction that is perpendicular to the shear direction.…”
Section: Summary and Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Due to dynamics in continuous shearing, this ordering phenomenon emerges even in systems composed of particles with very low platyness with a shape differing only slightly from spherical shape. This kind of ordering has previously been observed in experiments [27,22] and numerical simulations mainly with two-dimensional elongated particles [28,15,18]. Regarding the privileged direction of alignment, we found that, as platyness increases, this direction gradually changes from that of the major principal stress to a direction that is perpendicular to the shear direction.…”
Section: Summary and Discussionsupporting
confidence: 49%
“…This evolution of the privileged direction of alignment is consistent with several observations reported in Refs. [28,27,22].…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The behaviour of a single elongated free flowing intruder within a 2D layer of spheres has also been studied [7]. The elongation of particles in particular introduces many complexities such as the change in jamming transition, altering of shear strength parameters, the orientation of these particles with the principal stress region within sheared assemblies, and the strong dependence on initial conditions [5]. There exist no adequate models to explain these additional factors which are introduced into the rheology of granular materials by anisotropic shaped particles -even for relatively simple shapes such as ellipsoids or rods [5].…”
Section: Introductionmentioning
confidence: 99%
“…Many tests, both experimental and computational, have used spheres or cylinders due to the simplicity of those shapes [1] with glass beads often chosen for fundamental experiments. There have been studies conducted on systems entirely consisting of irregularly shaped or elongated particles [2][3][4][5], as well as the influence of mixtures of regular and elongated particles [6]. The behaviour of a single elongated free flowing intruder within a 2D layer of spheres has also been studied [7].…”
Section: Introductionmentioning
confidence: 99%